IJIN PENDIRIAN RUMAH SAKIT OLEH MODAL ASING BERKAITAN DENGAN PENGGUNAAN BAHASA ASING DALAM PENAMAAN RUMAH SAKIT - Ayu Prilia Diantari (University of Udayana, 2014)
The establishment of the hospital takes no small amount of capital and therefore theestablishment of the hospital does not relu out the possibility of the cooperation between foreigninvestors with local investors, the establishment of hospital procedures by foreign investors isregulated in health minister 147/MENKES/PER/2010 about the hospital licensing.The parties will establish a hospital must comply with the regulations contained in thearticles of ministerial regulation 147/MENKES/PER/2010.Regulation of the minister of healty in the attachment 147/MENKES/PER/2010 number 6mentioned for naming the hospital may not use language/foreign terms such as : “aninternational, world-class, global, but the reality in Bali and more hospital are using language/foreign terms in the naming of the hospital.